2014
DOI: 10.1002/ejoc.201402861
|View full text |Cite
|
Sign up to set email alerts
|

A Planar‐Chiral Phosphino(alkenyl)ferrocene for Suzuki–Miyaura C–C Coupling Reactions

Abstract: A simple method for the functionalization of closo‐borates [closo‐B10H10]2− (1), [closo‐1‐CB9H10]− (2), [closo‐B12H12]2− (3), [closo‐1‐CB11H12]− (4), and [3,3′‐Co(1,2‐C2B9H11)2]− (5) is described. Treatment of the anions and their derivatives with ArI(OAc)2 gave aryliodonium zwitterions, which were sufficiently stable for chromatographic purification. The reactions of these zwitterions with nucleophiles provided facile access to pyridinium, sulfonium, thiol, carbonitrile, acetoxy, and amino derivatives. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 145 publications
1
44
0
Order By: Relevance
“…Ferrocenylphosphines and 1,2‐disubtituted planar‐chiral ferrocenes are, for example, essential in the field of catalysis . Especially the synthesis of hindered biaryls by the Pd‐catalyzed C,C cross‐coupling reaction is still a challenging task, where ferrocenylphosphines bearing ortho ‐donor atoms or groups, for example oxygen,, aryl or vinyl,, have been shown to increase the catalytic activity. The vinyl fragment thereby acts as a hemi‐labile group, which enables the planar‐chirality of the ferrocenyl backbone to be transferred on a substrate, resulting in the formation of biaryls in an enantiomeric excess of up to 36 % .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrocenylphosphines and 1,2‐disubtituted planar‐chiral ferrocenes are, for example, essential in the field of catalysis . Especially the synthesis of hindered biaryls by the Pd‐catalyzed C,C cross‐coupling reaction is still a challenging task, where ferrocenylphosphines bearing ortho ‐donor atoms or groups, for example oxygen,, aryl or vinyl,, have been shown to increase the catalytic activity. The vinyl fragment thereby acts as a hemi‐labile group, which enables the planar‐chirality of the ferrocenyl backbone to be transferred on a substrate, resulting in the formation of biaryls in an enantiomeric excess of up to 36 % .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas a 1,2‐ P , O substitution pattern at ferrocene gave a five‐membered Pd complex (type A and B , molecules, Figure ), the introduction of a methylene linking unit increases the size to a six‐membered cycle ( C and D , , Figure ) . Increasing the steric demand of R from ethyl to (1 R )‐menthyl in the type C species, also enhanced the ee from 0 to 37 % (Figure ) .…”
Section: Introductionmentioning
confidence: 99%
“…The Suzuki-Miyaura reaction for the synthesis of hindered biaryls is a common test-reaction, whereby the ee of the formed coupling products expresses the transferability. [7] So far, a maximum ee of 54 % at catalyst loadings of low as 2 mol-% [Pd] could be reached. [3] biaryls, where sandwich compound (S p )-1-(PPh 2 )-2-(o-NMe 2 -C 6 H 4 )CH 2 -Fc gave an ee of 69 % (1 mol-% [Pd]), which is up to date the highest observed value for planar-chiral ferrocenes.…”
Section: Introductionmentioning
confidence: 99%
“…In our working group, ferrocenylphosphanes and planar‐chiral ferrocenylphosphanes,, were also investigated for the synthesis of congested biaryls by using the Suzuki–Miyaura C–C cross‐coupling reaction protocol , . Within these studies it could be shown that the use of ortho ‐vinyl,, and ortho ‐ether‐substituted, ferrocenylphosphanes increase the catalytic activity towards the synthesis of biaryls with sterically demanding substituents in the ortho position, due to a stabilization by a hemilabile binding of the ortho substituents . Use of the enantiomerically pure R p ‐isomer of the o ‐methoxyferrocenyl phosphine resulted in the formation of a racemic mixture of triple‐ ortho ‐substituted biaryls .…”
Section: Introductionmentioning
confidence: 99%